ANALISIS TINGKAT PENDIDIKAN DAN TPAK TERHADAP PDRB PERKAPITA DI INDONESIA - Affandi Affandi; Mirdha Fahlevi SI; Okta Rabiana Risma (JURNAL EKOMBIS, 2019)
This research would be to see the extent of the influence of education level and the participation rate of labour force on the PDRB per capita of Indonesian society. An education level indicator is a school participation number that consists of 19-24 years, 16-18 years, 13-15 years and 7-12 years and the workforce is measured through the labour force participation rate, while the production factor used by PDRB from 33 provinces in Indonesian. The method used is quantitative with time series 2010-2014 data and cross section 33 Province in Indonesia. Secondary Data is sourced from BPS. The analysis technique uses the data panel with the method Random effect model (REM). Research conclusion: (1) The PDRB per capita of 76.53 is influenced by the level of education and participation rate of labour force while the remaining 23.47 percent is influenced by other factors beyond this study. (2) APS ages 19-24, age 16-18 years and APS age 13-25 years positively and significantly impact the PDRB per capita in Indonesia. (3) APS ages 7-12 years and TPAK has a significant and negative impact on the PDRB per capita in Indonesia. Keywords: education level, workforce level, PDRB Percapita, Data Panel